SISTEM INFORMASI LOKASI PARIWISATA KABUPATEN ENDE BERBASIS WEB GIS - Azi , Waldetrudis Wea; Anggraini , Dewi (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2019)
Tourism is very important in sustaining local income. Tourism Department also required to develop tourism in the region, so as to attract tourists to visit the tourist attractions there. False one that should be developed is a geographic information system for the geographic information system of the tourists easily find tourist attractions. Ende, Flores Island is located in the central part has a beautiful natural scenery both sea and land, as well as tourism. Ende is known for a wide range of fascinating natural attractions, but the tourism potential has not been known by tourists who want to visit, because the Department of Tourism Ende in promoting tourist places are still using manual systems such as brochures, posters and books. Media is not sufficient to inform the tourist attractions widely. Because the Department of Ende requires an adequate promotional media such as web GIS so that travel is better known by local and foreign tourists. Researchers aim to build a location information system applications Ende tourism web based making it easier for travelers to find tourist spots in the district of Ende. Based on the above problems, the writer intend to design and build an information system of tourist sites in the district of Ende-based web, to help the Department of Tourism Ende in promoting tourist places in the district of Ende.